Cytotoxic Action of Serratia marcescens Hemolysin on Human Epithelial Cells - Hertle, Ralf (American Society for Microbiology, 1999)
Incubation of human epithelial cells with nanomolar concentrations of chromatographically purified Serratia marcescens hemolysin (ShlA) caused irreversible vacuolation and subsequent lysis of the cells. Vacuolation differed from vacuole formation by Helicobacter pylori VacA. Sublytic doses of ShlA led to a reversible depletion of intracellular ATP. Restoration to the initial ATP level was presumably due to the repair of the toxin damage and was inhibited by cycloheximide. Pores formed in epithelial cells and fibroblasts without disruption of the plasma membrane, and the pores appeared to be considerably smaller than those observed in artificial lipid membranes and in erythrocytes and did not allow the influx of propidium iodide or trypan blue. All cytotoxic effects induced by isolated recombinant ShlA were also obtained with exponentially growing S. marcescens cells. The previously suggested role of the hemolysin in the pathogenicity of S. marcescens is supported by these data.